An analysis of the technology management activities and future prospects of Robinsons Savings Bank - Castillo, Ma. Rowena Z. (University of the Philippines Diliman, 2004)
This is a project that aims to provide an assessment of the performance of Robinsons Savings Bank (RSB), one of the major thrift banks in the country today, for the past six years since it was established in October 1997. It also aims to give recommendations on how it could further improve its operations and profitability through Technology Management. The Project Background briefly discusses the current state of Banking in general, and how technology has changed the industry. Because of the fast-paced technological developments, even the finance sector has been undergoing rapid technological changes in order to remain competitive. Robinsons Savings Bank is no exception. The next section is the Statement of the Problem or what the study will attempt to answer after the project duration. The Statement of Objectives section gives the goals of the project; in other words, what the project will aim to accomplish. In the section on Significance of the Project, the benefits for Robinsons Savings Bank will be enumerated. The Methodology for working out the answers for the problem at hand will then be described in detail. This includes the conceptual framework, research design, data collection procedures, and planned data analysis process. The section on Project Results enumerates and discusses the specific outputs of the project. Finally, in the following sections, the Recommendations, Conclusion and Future Outlook for RSB will be stated.